The effect of debt attitude and peer influence on debt behavior - Dusia, Sheron Leviany; Setyabudhi, Kezia Natasha; Malelak, Mariana Ing (International Journal of Financial, Accounting, and Management, 2023)
Purpose: This study examined the effect of debt attitude and peer influence on the debt behavior of paylater users by the millennial generation. Research methodology: This study used a quantitative approach. The research method used in this study is a survey method. The instrument was a questionnaire made with Google Forms. The analysis method used in this research is Structural Equation Modeling (SEM), with Partial Least Squares (PLS) analysis technique using SmartPLS 3. The population was working millennials in Indonesia. Samples were chosen using a non-probability sampling technique with a purposive sampling method so that the total sample size was 100 people. Results: The results of this study proved that debt attitude had a significant effect on the debt behavior of paylater users of the millennial generation. However, peer influence had no significant effect on the debt behavior of paylater users by the millennial generation. Limitations: This study is limited to a few factors: debt attitude and peer influence. Moreover, this study only collects data from the junior millennial generation in Indonesia, which results in narrowing this study. Contribution: The information provided by this study can help authorities identify the determinants of debt behavior and address the rising debt levels.